Nanotechnology in the Treatment of Glioblastoma Multiforme: Enhancing Radiotherapy and Chemotherapy with Nanoparticles - Emilia Gabriela Chrzanowska; Jakub Paweł Kuźniar; Julia Szlążek; Adam Jan Ząbek; Michalina Zagalska; Marta Turek; Tomasz Tamborski; Adam Grzebinoga; Barbara Roguska; Michał Kuźniar (Journal of Education, Health and Sport)
Introduction: